Waiting for justice : human rights, justice, peace and reconcilation in Guyana and the world (1970 to 2008) - Trotman, Donald (Ashgrove House Publishers Golden Grove, ECDGY, 2008)
Presents a collection of selected writings of the author which have been delivered, presented or published over the last four decades. Seeks to address issues that span the spectrum of social and economic development in the Caribbean, from ideas of human dignity to the complexity of programmes, politicians and government officials devise to satisfy the social and economic expectations of the constituents.